The hidden inequalities of digitalisation in the post-pandemic context - Cristiano Codagnone; Maria Savona (Bruegel, 2023)
Digitalisation has a 'hidden' impact on employment, particularly on the invisible conditions of some jobs, as perceived by workers, that are relatively less explored in the literature and that could represent a substantial social cost, particularly in the aftermath of the financial crisis and the COVID-19 pandemic. We start by summarising a few main challenges of digitalisation, with a focus on the additional challenges brought about by the pandemic, the rise of platforms and alternative work arrangements, and the current attempts to regulate these. We then discuss the hidden aspects of inequality linked to the unmeasured side effects of digitalisation. Mental health in particular should be taken into account, particularly in the post-pandemic context, which has led to a significant amount of working from home. Also, the reduction of tasks previously done in the workplace in favour of remote working might limit social interactions, creativity and innovation potential. We conclude by suggesting areas for policy interventions.
Keywords: 330